Natural History and Long-Term Outcome of Patients Treated for Early Stage Colorectal Cancer - Hugh James Freeman (Canadian Journal of Gastroenterology)
BACKGROUND: The long-term natural history of early stage colon cancer and the outcome of long-term colonoscopic surveillance in routine specialist clinical practice after removal of the incident cancers have not been fully defined. In the present long-term evaluation up to 25 years, metachronous neoplasia, including both advanced adenomas and carcinomas, was defined.